Understanding of Authorship Guidelines and the Frequency of Authorship Misuse: A Descriptive Cross-Sectional Study in the State of Qatar - Seba Qussini (16727773) (2025)
Ethical authorship practices ensure both accountability and credibility. In this study, we estimated the frequency of encountering honorary and ghost authorship at least once among researchers at Hamad Medical Corporation (HMC) in Qatar. Additionally, we evaluated researchers’ familiarity with standard authorship guidelines. Using a cross-sectional design, we administered a pre-developed anonymous online survey to 4043 researchers. Descriptive statistics in the form of percentages and frequences along with a 2-sided Chi-square tests were used. Significance was defined as p ≤ .05. Overall, researchers demonstrated low awareness of adopted authorship guidelines. While 24% of respondents reported never having heard of the International Committee of Medical Journal Editors (ICMJE) guidelines, 76% were aware of them but unfamiliar with the content. Additionally, the low awareness coincided with reported frequencies of having encountered honorary and ghost authorship at least once—70.5% and 45.5%, respectively. In conclusion, authorship misuse is a significant issue in Qatar, and appears to occur at levels consistent with those found in international surveys. It remains a delicate matter that can be approached by promoting awareness, educating researchers, and encouraging adherence to guidelines. Other Information Published in: Journal of Empirical Research on Human Research Ethics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/15562646251395350